Evaluation of Impacted Mandibular Third Molars by Panoramic Radiography. (26th September 2010) - Gupta, Siddharth; Bhowate, Rahul R.; Nigam, Nitin; Saxena, Sonal
Abstract : Objective . The study was to evaluate impacted mandibular third molars (IM3M) for their angulation, level of eruption, third molar space and relation of inferior alveolar canal with their roots. Methods . Total 988 IM3M were studied in 578 individuals of age 18 years and above, dividing them into three groups i.e. symptomatic, asymptomatic and radiographic only. Individuals were also divided according to age, sex and side of IM3M (right or left). Panoramic radiographs were obtained after written consent and traced.ℵ 2 -test was applied to check inter-group and intra-group significance. Result . Out of 578 individuals 307 (53.11%) were males and 271 (46.89%) females. Maximum number of IM3M were in 18-27 years age group (398 i.e. 68.89%). Out of 988 IM3M, 39.93% were vertically placed. 61.84% IM3M were found at level A. Class II (79.65%) was the most common relation for third molar space. Notching (12.55%) was most common true inferior alveolar canal and IM3M root relation whereas superimposed (41.80%) was most common false inferior alveolar canal and IM3M root relation. For all the criteria significant inter-group difference was found (consideringP < .05 ) and intra-group difference was non significant. Conclusion and significance . Panoramic radiographs can be used as reliable investigation for evaluation of IM3M.